Análisis de la gestión de los servicios turísticos que ofrece el Santuario Histórico Bosque de Pómac en la Provincia de Ferreñafe, Región Lambayeque - Gibson Capristan, Diana Pilar (2017)
The present investigation addresses the problematic of the tourist services of the Historic Sanctuary of Pomac. At the first phase of the investigation we made a description of the area of study wich includes thegeographic location and accessibility. In addition, an analysis of the national, regional and local context was done to understand the current state of the forest and the services. Also, as a fundamentar part of the research, planning and management are analyzed through a mapping of stakeholders to identify their interrelationships. Besides the research includes a detail of the diferents areas of the Sanctuary with the goal of recognizing in which area tourist services can be provided. At the second phase of the investigation, the research analized the origin, attractions, supply and demand of the product named “Bosques y Pirámides” to conclude with a proposal of improvement. This is due to the fact that the Historic Sanctuary of Pomac is part of this national product. Finally, at the third phase of investigation, after analyzing the touristic proficle who visit the Sanctuary, we proceed to make some recommendations to improve the tourist services. It shoul be noted that this thesis is a qualitative analysis that seeks to generate the further development of quantitave analysis.